Covid-19 and Intensive Care Unit: Infection, Contact Time & Procedures Performed - Waqas Aslam, Fariha Salman, Syed Mazhar Ali Naqvi, Humaira Nazir, Anam Ahmad, Sohail Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Safety of front-line health care workers dealing with critically ill patients is of prime importance during COVID-19 pandemic. We have limited skilled workforce and intensive care units (ICU). Aim: To determine the frequency of COVID 19 among ICU staff and find association with contact time and procedure performed. Methods: A comparative cross-sectional study was conducted on 95 subjects working in ICU settings of tertiary care hospitals of Lahore. Data was collected about COVID-19 infection, prevention practices, contact time & procedures performed through google forms. Data was entered & analyzed by SPSS v23 while performing descriptive statistics, T Test, Chi square test & binary logistic regression. Results: Among 95(100%) subjects 25(26.31%) had covid-19 infection whereas 70(73.68%) did not had infection. Age> 30(p=.041), female gender (p=.022), use of re-useable personal protective equipment PPE(p=.009), contact time (p=.020), performing procedures: Nebulization(p=.023) & non-invasive positive pressure ventilation (p=.011) were significantly associated with COVID-19 infection among ICU staff. Conclusion: There was high frequency of COVID-19 infection among ICU staff. Age> 30, female gender, re-useable PPE, contact time, performing procedures: Nebulization & non-invasive positive pressure ventilation were significantly associated with COVID-19 infection among ICU staff. Keywords: COVID-19, Contact time, Intensive care unit, Infection, Procedures